Umur Simpan Nugget Ikan Tuna Substitusi Daun Kelor dan Wortel dengan Metode Extended Storage Studies - Juhartini Juhartini; Nurbaya Nurbaya; Radawati Laidi (Politeknik Kesehatan Kemenkes Mamuju, 2022)
The nutritional status of under-five children in Indonesia remains low, including in North Maluku province. Based on the results of the 2021 SSGI, the prevalence of stunting among under-five children in this province is 27.5%. This figure is higher than the national prevalence of 24.4%. North Maluku has abundant potential for tuna fish that can be utilized in the development of local food that supports nutritional interventions for children. The recent study reported that as many as 86.7% of children aged 12 – 24 months consumed processed foods like nuggets, sausages, and meatballs. Most consumers (98.67%) also showed a high interest in consuming nuggets that contain higher protein and mineral content. The addition of moringa leaf vegetables and carrots to nuggets will increase the nutritional content of nuggets which can increase nutritional intake for children. This study was an experimental study that aimed to determine the shelf life of tuna fish nuggets substituted with moringa leaves and carrots using the Extended Storage Studies (SES) method. SES method was used to determine the shelf life of tuna fish nuggets substituted with moringa leaves and carrots by looking at the organoleptic quality which includes aroma, color and texture. Observations were made in February-March 2021 for 60 days at the Laboratory of Food Science, Poltekkes Ternate. Changes in quality began to occur on the 35th day of observation, namely the texture of the nuggets began to not be crunchy. While the observation of color and aroma did not change until the 60th day of observation. In conclusion, the shelf life of tuna fish nuggets substituted with Moringa leaves and carrots is up to 30 days.